1991
DOI: 10.1111/j.1365-2273.1991.tb01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirating middle ear effusions when inserting ventilation tubes: does it influence post-operative otorrhoea, tube obstruction or the development of tympanosclerosis?

Abstract: This prospective study examined the influence of aspirating middle ear effusions, immediately prior to ventilation tube insertion, upon the subsequent development of otorrhoea and tympanosclerosis. 50 children were studied and aspiration of effusions did not influence the incidence of purulent otorrhoea or ventilation tube obstruction within 1 month of surgery. The development of tympanosclerosis did not correlate with effusion aspiration, but in those ears which had an effusion aspirated there was a relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
4
21
0
1
Order By: Relevance
“…This result was independent of the extrusion times of the ventilation tubes. In the study by Dawes et al, 3 tympanosclerosis was found to have developed in 48.6 per cent of all ears at 18 months post-operatively. There was no overall difference between the two groups.…”
Section: Tympanosclerosismentioning
confidence: 94%
See 1 more Smart Citation
“…This result was independent of the extrusion times of the ventilation tubes. In the study by Dawes et al, 3 tympanosclerosis was found to have developed in 48.6 per cent of all ears at 18 months post-operatively. There was no overall difference between the two groups.…”
Section: Tympanosclerosismentioning
confidence: 94%
“…2 It has been suggested that this technique improves hearing immediately after the operation by relieving the mechanical obstruction caused by the effusion and also prevents viscid secretions from obstructing the ventilation tube. 3 At present, there is no clear evidence to suggest that the aspiration of middle-ear effusion is associated with a better clinical outcome in terms of hearing improvement and tube patency. Concerns about the safety of middle-ear effusion aspiration have been expressed over the years, including the possibility of acoustic trauma to the inner ear due to suction noise 2,4 and the increased risk of tympanosclerosis resulting from the additional mechanical trauma of clearing the effusion, causing inflammation and bleeding of the tympanic membrane.…”
Section: Introductionmentioning
confidence: 98%
“…Tos et al [5] stated that reduced mobility of the tympanic membrane in the ear with inflammatory fibrous hyperplasia promotes hyalinization and calcification in the collagen layer. Similarly Dawes et al [18] hypothesized that the risk of development of MS is increased where there is traumatic tube insertion, hemorrhage, or excessive aspiration of middle ear fluid.…”
Section: Discussionmentioning
confidence: 97%
“…12 In myringotomy with VT insertions, there intraepithelial bleeding may occur and healing with fibrosis will be happened. 13 Studies suggested that the ear canal bleeding may lead to myringosclerosis development in the long term, so reducing the hemorrhage during myringotomy can minimize the myringosclerosis development in the long term. 14 The incidence of tympanosclerosis after VT insertion ranged from 25 to 35% in the literature.…”
Section: Introductionmentioning
confidence: 99%